PENGARUH MODEL CONTEXTUAL TEACHING AND LEARNING (CTL) TERHADAP HASIL BELAJAR SISWA PADA PEMBELAJARAN IPAS KELAS V DI SD NEGERI 37/II PASAR LUBUK LANDAI - Muhammad Sukron; Muhammad Subhan; Dias Pebriyani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research was motivated by the low learning outcomes of students in science learning, this is because the users of the learning model applied by the teacher are still not optimal and the learning model used is not varied so that students feel bored and passive in class. This study aims to determine the effect of the Contectual Teaching and Learning (CTL) Model on Science Learning Outcomes in Class V at SD NEGERI 37/II Pasar Lubuk Landai, Bungo Regency. This type of research is Pre Experiment Design research. With a quantitative approach and the form of design using a Quasi-Experimental Non-Equivalent Group Pre-test Post-test Design method. The subjects of this study were fifth grade students of SD Negeri 37/II Pasar Lubuk Landai. The sampling of this research used the probanility Sampling technique, which consisted of 30 students. The data collection technique was done by using test and non-test techniques. The data collection tool is in the form of multiple choice questions, totaling 20 items for pre-test and post-test through validation test. And reability test. Data were analyzed using the Normality Test and Hypothesis Testing/t-test processed using SPSS 23.The results of the calculation of the hypothesis test sig<(0,000<0,05) which means the t-test resjects the existence of H0 and accepts Ha, which means that there is an Influence of Contextual Teaching and Learning (CTL) Model on Science Learning Outcomes in Class V at SD Negeri 37/II Pasar Lubuk Landai Bungo Regency.